2021
DOI: 10.1007/s11104-021-04897-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cover crops and soil microorganisms increase phosphorus availability in conservation agriculture

Abstract: Aims An essential task of agricultural systems is to improve internal phosphorus (P) recycling. Cover crops and tillage reduction can increase sustainability, but it is not known whether stimulation of the soil microbial community can increase the availability of soil organic P pools. Methods In a field experiment in southwest Germany, the effects of a winter cover crop mixture (vs. bare fallow) and no-till (vs. non-inversion tillage) on microbial P-cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 105 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…Cover crops: Over the last decade, the increased use of cover crops between growing seasons has motivated the inclusion of this practice in the field experiments of many study sites. The benefits of cover crops are generally well accepted, and recent research has indicated that they can also enhance the availability of soil P and have positive effects on the soil microbial community [121][122][123] and earthworm abundance [116]. Positive effects were also illustrated by experiments in the study sites in Norway, Portugal, Denmark, France, Italy, and Germany [79].…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…Cover crops: Over the last decade, the increased use of cover crops between growing seasons has motivated the inclusion of this practice in the field experiments of many study sites. The benefits of cover crops are generally well accepted, and recent research has indicated that they can also enhance the availability of soil P and have positive effects on the soil microbial community [121][122][123] and earthworm abundance [116]. Positive effects were also illustrated by experiments in the study sites in Norway, Portugal, Denmark, France, Italy, and Germany [79].…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…The ability of some CF species belonging to the genera Talaromyces, Penicillium, and Purpureocillium as P solubilizers have been reported [42][43][44]. The two main mechanisms involved in P solubilization by microorganisms are the synthesis of phosphatase and phytase enzymes [45][46][47][48] and the release of organic acids such as oxalic, citric, acetic, succinic, and lactic [48][49][50][51] during the decomposition process. Data is represented by the mean±SE (n=3).…”
Section: Phosphorusmentioning
confidence: 99%
“…Symbiotic interactions between soil microorganisms and various crops (e.g., mycorrhizae) protect crops from pathogenic fungi and enhance stress tolerance relating to drought [217]. However, soil microorganisms are influenced to a marked degree by crop management [218,219]. Pesticides usually evoke at least a short-term negative response in soil microorganisms and many soil animals, e.g., earthworms [220].…”
Section: Impact On Natural Regulatory Processesmentioning
confidence: 99%